The current level of research on the possibilities of ensuring access to justice - Drakokhrust, Tetiana; Homotiuk, Andrii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article explores the contemporary state of research concerning the potential methods for ensuring access to justice. It delves into the multifaceted aspects of this subject, including the procedural elements of court systems, the appointment and support of qualified individuals in judicial positions, and the various procedures associated with initiating and resolving cases. The research emphasizes the importance of legal codification in guaranteeing not only access to the court but also ensuring fair and impartial judicial reviews, ultimately serving the primary goal of safeguarding the rights and legitimate interests of individuals. Furthermore, the article highlights a specific focus on criminal justice, with scholars, particularly V. Shybiko, positing that access to justice is an autonomous principle within criminal procedures, rooted in the broader human right to judicial protection. Overall, the research underscores the significance of ongoing scholarly investigations into the diverse dimensions of access to justice, acknowledging its foundational role in effective procedural legislation and its intrinsic connection to broader human rights principles.